Vibrational energy transfer via modulated impacts for percussive drilling - Wiercigroch, Marian; Krivtsov, Anton M.; Wojewoda, Jerzy (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2008)
In this paper, a new method of vibrational energy transfer from high- frequency low-amplitude to low-frequency high-amplitude mechanical vibrations is proposed and investigated, for the purpose of percussive drilling. The mechanism uses an impact loading comprised of two frequencies forming a beat which excites a structure tuned to the beat-frequency. This concept has been modelled and experimentally verified. It is postulated that the efficiency of this technique is strongly dependent on the strength of nonlinearity in the system. The vibrational energy transfer is significantly reduced for superharmonic responses of the system. Practical applications of this mechanism can been seen as new generation percussive drilling tools.

W niniejszej pracy zaproponowano i pokazano wyniki nowego sposobu transferu energii z obszaru drgań o wysokich częstościach i małych amplitudach w obszar niskich częstości i dużych amplitud. Badania przeprowadzone były pod kątem zastosowań w wierceniu udarowym. Mechanizm działania wykorzystuje obciążenie uderzeniami modulowane kombinacją dwu częstości tworzących obwiednię w kształcie dudnienia o strukturze dostrojonej do częstości uderzeń. Pokazano opracowany model i wyniki jego weryfikacji eksperymentalnej. Wydaje się, że wydajność tej techniki jest mocno zależna od siły nieliniowości w układzie. Transfer energii drgań jest mocno zmniejszony dla superharmonicznych odpowiedzi układu. Możliwe jest praktyczne zastosowanie tego mechanizmu w nowej generacji wierteł udarowych.
Transfer energii drgań poprzez modulowanie uderzeń w wierceniu udarowym
Keywords: vibration; energy transfer; impacts; experimental studies; uderzenie; drgania; przenoszenie energii; wiercenie udarowe; wiertła udarowe; transfer enrgii drgań